Mizoribine is as Effective as Methotrexate for the Treatment of Polymyalgia Rheumatica: A Retrospective Case Series Analysis - Kazushige SHIRAISHI,; Masei SUDA,; Ryo ROKUTANDA,; Mitsumasa KISHIMOTO,; Masato OKADA, (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the efficacy and safety of mizoribine (MZR) as a steroid-sparing agent compared to methotrexate (MTX) in the treatment of polymyalgia rheumatica in elderly patients. Patients and methods: Twenty-four patients (9 males, 15 females; mean age 71.7 years; range 50 to 86 years) diagnosed with polymyalgia rheumatica between April 1998 and August 2014, who received prednisone in combination with either MTX or MZR, were included. We collected the data on the cumulative prednisone dose that patients received within 48 weeks after MTX or MZR and its side effect profile. Results: There were 10 patients in the MTX group and 14 in the MZR group. The cumulative prednisone dose over 0-48 weeks was 2272±396 mg in the MTX group and 1907±241 mg in the MZR group, which was not significantly different (p=0.41). In terms of side effects, in the MTX group, three patients experienced a transient elevation in liver enzymes, and one patient developed gastrointestinal symptoms that led to MTX withdrawal. In the MZR group, one patient was hospitalized due to pneumonia that led to MZR withdrawal. Conclusion: Mizoribine was non-inferior to MTX in terms of steroid-sparing effects on polymyalgia rheumatica. Also, MZR tended to have fewer side effects than MTX.